Modeling colorectal cancer progression reveals niche-dependent clonal selection - Vaquero Siguero, Nuria; Schleußner, Nikolai; Volk, Julia; Mastel, Manuel; Meier, Jasmin; Jackstadt, René-Filip (Cancers, 2022)
Colorectal cancer (CRC) is among the deadliest cancers worldwide, with metastasis being the main cause of patient mortality. During CRC progression the complex tumor ecosystem changes in its composition at virtually every stage. However, clonal dynamics and associated niche-dependencies at these stages are unknown. Hence, it is of importance to utilize models that faithfully recapitulate human CRC to define its clonal dynamics. We used an optical barcoding approach in mouse-derived organoids (MDOs) that revealed niche-dependent clonal selection. Our findings highlight that clonal selection is controlled by a site-specific niche, which critically contributes to cancer heterogeneity and has implications for therapeutic intervention.
Gesehen am 26.10.2022